Osteoradionecrosis after mandibular reconstruction: a comparative cohort study on quality of life and complications - Zhang, Peng; Lu, Taiqing; Gu, Ruiyan; Yang, Wenli (Frontiers in Oncology, 2026)
ObjectiveThis study aimed to compare longitudinal quality of life (QoL) and surgical outcomes following segmental mandibulectomy and free fibula flap reconstruction among patients with osteoradionecrosis (ORN), malignant disease, and benign conditions.MethodsA comparative cohort study was conducted involving 245 patients: 45 with ORN, 160 with malignancy, and 40 with benign disease. Patient-reported QoL was assessed using the EORTC QLQ-C30 and QLQ-H&N35 questionnaires preoperatively and at 3, 6, and 12 months postoperatively. The primary outcomes were 12-month Global Health Status (QLQ-C30) and Pain scores (QLQ-H&N35), analyzed using multivariable linear regression. The secondary outcome was the incidence of major surgical complications (Clavien-Dindo ≥ III), analyzed using multivariable logistic regression.ResultsAt 12 months, the ORN cohort demonstrated significantly worse QoL outcomes compared to the benign cohort, with a -14.1-point lower Global Health Status (95% CI: -19.5 to -8.7, p<0.001) and a +21.5-point higher Pain score (95% CI: +15.2 to +27.8, p<0.001), after multivariable adjustment. The ORN cohort also had the highest rate of major complications (48.9% vs. 17.5% benign, p<0.001), which remained significant in multivariable analysis (aOR for benign vs. ORN: 0.26, p=0.006). Larger bony defect length and longer operative time were independent predictors of poorer QoL and higher complication risk, while the use of virtual surgical planning was associated with better Global Health Status.ConclusionDespite successful reconstruction, patients with ORN experience profoundly poorer long-term QoL, persistent pain, and a significantly higher complication burden compared to patients with benign or malignant disease. These findings highlight the unique challenges in ORN management and underscore the need for specialized long-term supportive care.